ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PILIHAN KARIR MAHASISWA AKUNTANSI SEBAGAI AKUNTAN PUBLIK - Ilham, Zain Muhammad (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to identify accounting students’ interest of becoming public accountants. This quantitative research was conducted in four universities in East Java, namely Universitas Brawijaya, Universitas Airlangga, Muhammadiyah University of Malang, and Surabaya University. The data was collected by distributing questionnaires asking responses about the influence of salary, gender, university of origin, family, and city of origin. This study finds that in general accounting students are still interested to become public accountants. Furthermore, this study also finds that gender does not determine the interest of accounting students to become public accountants.Keywords: interests, public accountants, student